Georgia : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Recent Economic Developments and Selected Issues paper on Georgia highlights that during 1997, the Georgian economy grew by 11 percent according to official estimates, while the average annual inflation rate continued its downward path initiated in 1995 and reached single-digit levels of about 7 percent. The fiscal deficit (on a commitment basis) declined from 4.5 percent in 1996 to 4.1 percent in 1997. Investment outlays of the general government, however, fell in real terms in 1997 as the government adjusted to a tighter budget constraint.